Hierarchy of needs and subjective wellbeing - Abu Bakar, Aisyah (Malaysian Institute of Planners, 2022)
Maslow's hierarchy of needs and Subjective Well-Being (SWB) are the two concepts that this paper addresses. The SWB measures used include Eudaimonic Wellbeing (EWB), Human Functioning (HF), and Satisfaction with Life (SWL). Issue: A range of human needs must be fulfilled in order to maintain SWB. However, SWB is not always dependent on the criteria that were considered significant; rather, it depends on the factors that respondents believe are most significant based on their cognitive assessments. Furthermore, people do not have to fully satisfy one need for the subsequent need to rise in the hierarchy. Purpose: In order to determine how SWB relates to the convenience and difficulty of meeting human needs, this study delves into such relationships. Method: Mann Whitney U-Tests were implemented to determine the median SWL across 24 human needs, accounting for both convenience and difficulty. These basic requirements for life are what people typically and widely strive for. Findings: SWB increased by how convenient the majority of human needs can be satisfied. The SWB did not significantly interact with some human needs, despite their being regarded vital.